Broader impacts of the fare-free public transportation system in Tallinn. Issue 3 (2nd September 2019) - Gabaldón-Estevan, Daniel; Orru, Kati; Kaufmann, Clemens; Orru, Hans
ABSTRACT: In this paper, we focus on the rationale for implementing the fare-free public transportation system (FFPTS) in Tallinn, Estonia, that took place on 1 January 2013. Through a series of interviews with relevant informants, we identify the main enablers and the FFPTS in Tallinn faced and the potential of such a system to contribute to the sustainable city development. Our analysis shows that the interlinking between local and national politics determines not only the type of initiatives implemented and the support they receive but also the degree of their success and their stability. We conclude that to be even more effective, it should be extended to the all potential users, not just to local registered residents as it has been recently applied in state-run bus travels in rural municipalities in Estonia. Finally, more restrictive private car policies should be considered to fuel a sustainable mobility transition and increase cities life quality.